Perubahan Perilaku Pemberantasan Sarang Nyamuk Demam Berdarah Dengue (DBD) Di Wilayah Cipayung Jakarta Timur - Yeny Sulistyowati; Cicilia Windiyaningsih; Tiwi Nurhastuti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Based on data from the Indonesian Health Profile in 2017 there were 433 districts / cities infected with dengue disease with an incidence rate of 68,407 cases with 493 deaths (Ministry of Health RI, 2018). Meanwhile, for the DKI Jakarta Province area, the highest number of dengue sufferers in 2017 was in the East Jakarta area of 1,265 cases (DKI Jakarta Health Office, 2018). Riskesdas data in 2018 shows the proportion of Mosquito Nest Eradication (PSN) carried out by households as a whole in Indonesia the proportion is 31.2% and for DKI Jakarta province itself the proportion is 28%. In the implementation of PSN, it is differentiated based on urban and rural areas, for urban areas the proportion is 32.7% and for rural areas the proportion is 29.4%. (Riskesdas, 2018). Data on dengue cases in the Cipayung District Health Center area in 2016 amounted to 623 cases, in 2017 it dropped to 78 cases, in 2018 it dropped again to 52 cases, but in early 2019, from January to March, it increased to 152 cases, and the Cipayung District Health Center was included in the first rank of the highest dengue cases in the East Jakarta region (Cipayung PKC Surveillance, 2019). The activity was held online, on Wednesday, November 4, 2020. The number of participants was 367 people. After 3 months, the change in behavior of PSN DBD COMBI was evaluated and communicated again the change in the hope that dengue cases would decrease significantly. The output of this service activity is https://jakarta.tribunnews.com/2020/11/04/200-peserta-ikuti-webinar-lppm-urindo-bahas-tuntas-penyakit-menular, URINDO Website in News: urindo.ac.id and on Youtube URINDO. In addition, there was an increase in community empowerment (1), knowledge increased in support attitudes and dengue cases decreased. Keywords: Community Empowerment, PSN, DHF